SUFISM IN THE PERSPECTIVE OF THE QUR'AN AND HADITH - Nurul Azizah; M. Aris Faisol (Pascasarjana Universitas Wahid hasyim Semarang, 2020)
Abstract An understanding of the inner element is also called Sufism. It is from the Qur'an and the Sunnah that the Sufis first base their opinions on morals and behavior, longing and love for God, makrifat, suluk (path), as well as spiritual practices. This research is library research that aims to analyze